Optimum Financing Portfolio Of Islamic Microfinance Institutions: Indonesia Case - MAWARDI, I.; WIDIASTUTI, T.; SUKMANINGRUM, P. S; AL MUSTOFA, M. U (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The purpose of this paper is to analyze the risk-return of financing and find the optimum financing instruments portfolio of Islamic microfinance institutions (IMFI).The optimum portfolio financing is determined by the minimum coefficients of variation of financing instruments portfolio, namely Murabahah, Mudharabah-Musyarakah, and Ijarah. The methodology of this study is quantitative, which is using risk and return theory to compute risk, return, variance, and coefficient of variation of financing instruments portfolio. The solver program of Microsoft Excel is used to find the optimum combination and composition of financing portfolio. This research found that ijarah financing has the highest return.RESUMEN El propósito de este documento es analizar el retorno del riesgo del financiamiento y encontrar la cartera óptima de instrumentos financieros de las instituciones de microfinanzas islámicas (IMFI). La financiación óptima de la cartera está determinada por los coeficientes mínimos de variación de la cartera de instrumentos de financiación, a saber, Murabahah, Mudharabah-Musyarakah e Ijarah. La metodología de este estudio es cuantitativa, que utiliza la teoría del riesgo y el rendimiento para calcular el riesgo, el rendimiento, la varianza y el coeficiente de variación de la cartera de instrumentos financieros. El programa de solución de Microsoft Excel se utiliza para encontrar la combinación óptima y la composición de la cartera de financiación. Esta investigación encontró que el financiamiento de ijarah tiene el mayor rendimiento.